Differences in MCT1 A1470T polymorphism prevalence between runners and swimmers - Ben-Zaken, S.; Eliakim, A.; Nemet, D.; Rabinovich, M.; Kassem, E.; Meckel, Y. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Skeletal muscle is the major producer and user of lactate in the body. Therefore, transport of lactate across cells' membrane is of considerable importance. Lactate transport is mediated by proton-linked monocarboxylate transporter (MCT1). The A1470T polymorphism (rs1049434) in MCT1 gene influences lactate transport, with T allele associated with reduction of lactate transport rate and elevation in blood lactate levels. The aim of the current study was to compare allelic and genotype frequencies of MCT1 A1470T polymorphism among Israeli track-and-field athletes, swimmers, and non-athletes. Genomic DNA was extracted from 173 track-and-field athletes (age 17-50), 80 swimmers (age 16-49), and 128 non-athletes (age 19-29). Track-and-field athletes were assigned to three subgroups: long-distance runners, middle-distance runners, and power event athletes. Swimmers were assigned to two subgroups: long-distance swimmers and short-distance swimmers. Genotyping was performed using polymerase chain reaction. T-allele frequency was significantly higher among long-distance swimmers (45%) compared with long- and middle-distance runners (27% and 30%, respectively; P < 0.01). In addition, T-allele frequency was significantly higher among short-distance swimmers (40%) compared with power event athletes (25%, P < 0.01). Overall, T-allele frequency was significantly higher among swimmers (42%) compared with runners (27%, P < 0.001). More research is needed to clarify whether this polymorphism displays advantage for swimming performance.